Delusions and the madness of the masses - Reznek, Lawrie (Rowman & Littlefield, 2010)
According to the author, there is an alarming inclination for people to succumb to delusional thinking. Contrary to popular opinion, such thought processes are not limited to the mentally ill. Instead, there is growing evidence to show that large segments of the public harbor a wide variety of delusions, none of which are innocent, and many of which are pushing our societies to the brink of war. This book aims to understand the nature of delusions and how they are generated. By providing a deeper understanding of delusions, the author challenges the assumption that a whole community cannot be.